The Complexities of the Narrator Persona in Historiography – the Case of Sallust’s Bellum Catilinae - Pobežin, Gregor (2019)
This paper explores the complex persona of the narrator in historiographic texts. It would seem that in historiography, the narrator should be a rather straightforward notion, since it is generally assumed that historiographic texts ideally represent something that actually happened in the past. A historiographic narrator should be, according to the prevailing doctrines, a reliable and coherent intratextual function that must always stay outside the reported story, which bestows on him/her a cloak of omniscience. Yet in some of the most important historical works, the narrator proves to be less than a stable and reliable instance.
Keywords: Thucydides; Sallust